1982
DOI: 10.1677/joe.0.0950357
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, growth and oestradiol-receptor levels of 7,12-dimethylbenz(a)anthracene-induced mammary tumours in rats: effects of neonatal sex steroids and oestradiol implants

Abstract: The effects of neonatally administered steroids on the sensitivity of the mammary gland to tumour induction by 7, 12-dimethylbenz (alpha) anthracene was studied as a model for delayed (de) differentiating effects of steroid hormones. Immediately after birth male and female rats were gonadectomized and treated with testosterone, oestradiol or oil. Control animals were left intact. On day 45 all the gonadectomized animals and some of the control animals received an implant which delivered continuous low levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Our findings are consistent with the fact that ligands can alter the number/function of a receptor when they are present, and generally do not cause any persistent changes in receptor expression. One exception is an exposure that occurs during fetal life or immediately after birth, which can produce a permanent change (Verhoeven et al, 1982;Bern et al, 1985;Hilakivi-Clarke et al, 1998). However, since a prepubertal treatment with both a low (interacts with ER) and high (interacts with ER and other targets) dose of genistein or zearalenone reduces subsequent mammary tumorigenesis, prepubertal ERs may be involved as mediators of these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with the fact that ligands can alter the number/function of a receptor when they are present, and generally do not cause any persistent changes in receptor expression. One exception is an exposure that occurs during fetal life or immediately after birth, which can produce a permanent change (Verhoeven et al, 1982;Bern et al, 1985;Hilakivi-Clarke et al, 1998). However, since a prepubertal treatment with both a low (interacts with ER) and high (interacts with ER and other targets) dose of genistein or zearalenone reduces subsequent mammary tumorigenesis, prepubertal ERs may be involved as mediators of these effects.…”
Section: Discussionmentioning
confidence: 99%
“… Yoshida and colleagues [ 55 ] SD rats TP 1.25 Daily until the end of the experiment ? Purnell [ 56 ] LEW/Mai rats TP 1.25 Single injection No effect Verhoeven and colleagues [ 57 ] Female and male SD rats TP 0.5 Single injection No effect SD, Sprague?Dawley; TP, testosterone propionate. a Female rats unless otherwise specified.…”
Section: Effects Of Androgens In Rodent Breast Cancer Modelsmentioning
confidence: 99%
“…DMBA-induced tumor incidence has also been examined after neonatal androgenization of female rats (Table? 3 ) [ 52 ]-[ 57 ], with androgens first injected between 0 to 5?days after birth and treatment varying from a single injection to continuous treatment until the end of the experiment. Most studies [ 52 ]-[ 55 ], but not all [ 56 ],[ 57 ], found that, like peri-pubertal treatments, neonatal androgenization reduced tumor incidence.…”
Section: Effects Of Androgens In Rodent Breast Cancer Modelsmentioning
confidence: 99%
“…Verhoenven et al performed gonadectomy to neonatal male and female rats and immediately treated some of the animals with a single dose of T or E2 [98]. These animals did not show significant change in the incidence of DMBA-induced mammary carcinomas, compared to the gonadectomized rats without treatment of T or E2.…”
Section: Uses Of Androgens In Womenmentioning
confidence: 99%